Attitudes of the European printing industry towards innovative combinations of print and digital - Tiekstra, Sanne; Držková, Markéta; Miranda, Paula; Isaías, Pedro; Vehmas, Kaisa; Seisto, Anu (My University, 2016)
The present study reports a European industry survey of the state and future of innovative printing. In this study, we have defined innovative printing as printed electronics, printed intelligence, printed functionalities, combining print with digital (e.g. providing digital solutions for Quick Response codes or augmented reality), and similar products and services. Experiences and inputs from industry representatives were collected through a survey to provide viewpoints on how print media and packaging could be developed and used in the future and how the industry can utilize this knowledge from the academia for the benefit of their customers and the consumers. Based on the results, it may be concluded that (1) European graphical companies do see a possible future in innovative printing, (2) besides the possibility of increased costs, the lack of market demand is the most important factor preventing companies embracing this technology, and (3) in general the approach and vision of the industry is similar across all of Europe. However, Western European printing houses appear to be more active in the field of innovative printing as defined here, whilst in Eastern Europe the technology is currently focusing on special effects and personalized printing, suggesting a possible delay in the implementation of innovative printing technologies as a whole.
Postoje evropského tiskového průmyslu k inovativním kombinacím tisku a digitálních technologií
Keywords: Innovation, Printing; Europe; Prospective study; inovace; tisk; Evropa; prospektivní studie